QoS support and performance analysis of the PetaWeb optical network - Huang, Aimin (University of Ottawa (Canada), 2003)
With the dramatic increase of Internet users and the development of new high volume Internet applications, both the volume and dynamic behavior of the Internet traffic has changed. Services based on high-bandwidth multimedia applications will be the dominant sources of traffic in the future. In order to cope with the immense diversity of applications and traffic volume, highly dynamic optical networks will be needed. Recently, optical network technologies have dramatically advances due to several major developments such as Dense Wavelength Division Multiplexing (DWDM), innovative Optical Amplifiers (OA), and wavelength switch. These set the foundation for the Next Generation Optical Networks (NGON) and have profound impact on the design of NGON architectures and technologies. The research work in this thesis focuses on an alternative next generation optical network architecture, to be operated at multiple petabits per second speeds, called PetaWeb network. The PetaWeb simulation model is implemented, the network functionalities are verified and the network performance metrics involving tandem traffic, reconfiguration period, the number of channel and channel granularity, and the traffic variation are quantified. Furthermore, in order to provide Quality of Service (QoS) over the PetaWeb network, the QoS-Aware edge node and the QoS-Aware channel allocation algorithm are proposed. The performance of the QoS-Aware PetaWeb network is also evaluated and analyzed through simulations.
Keywords: Engineering, Electronics and Electrical.